CYBERCULTURE PADA APLIKASI KENCAN ONLINE YANG MEMUNCULKAN AKUN ANONIM PELAKU KBGO PADA WANITA URBAN - Pradypta, Anindya (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
This research aims to describe Kekerasan Berbasis Gender Online (KBGO) that is still perceived as insufficiently recognized by vulnerable or at-risk individuals, especially women as a group prone to becoming victims. Based on the Instagram account @aliskamugemash, which collects stories from victims of a perpetrator who has an excessive interest (fetish) in the eyebrows of his victims. Initially, the perpetrator and the victims meet through online dating applications (such as Tinder, Bumble, OkCupid, and others) but the perpetrator uses a fake identity or alter account. This research utilizes ethnographic methods and is supported by cyberculture theory, social exchange theory (exchange story), and identity theory. With the existence of OGBV victims among urban women, education about OGBV becomes crucial because urban women, who have easier access to internet data and adequate education, still have the potential to become victims of KBGO.